Rekayasa Perubahan Warna Melalui Penambahan Tepung Spirulina platensis Pada Pakan Terhadap Intensitas Warna dan Pertumbuhan Ikan Cupang (Betta Splendens) - Sahidi, Bela Findisia; Kusuma, Pungky Slamet Wisnu (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Betta fish is a freshwater ornamental fish with a unique body shape and the brightness of its color is one of the attractions among its fans. The increase in color intensity and growth in betta fish is greatly influenced by the nutrient content in the feed and genetics. Adding Spirulina platensis flour to feed is expected to increase feed nutrients such as beta carotene, which is known to increase the intensity of color and growth of betta fish. This study aims to prove whether adding Spirulina platensis flour to feed can increase the intensity of color and growth of betta fish. The experimental research used a Complete Random Design (RAL) with 4 treatments and 3 replicates, namely P0 (0%), P1 (3%), P2 (5%), P3 (7%) for 3 months. The parameters measured were color intensity and growth. Test F to determine the effect of treatment on parameters, if there is a real influence, the Duncan test is carried out The test fish in the study is a one-month-old, blue, and male betta fish seed. The results showed that the addition of Spirulina platensis flour to P1 treatment feed (3%) experienced the highest increase in color intensity (P<0.05) followed by P2 treatment (5%), then P3 treatment (7%) and finally P0 treatment (0%). The P1 treatment (3%) was shown to be optimal in increasing the intensity of the color of betta fish but was not followed by an increase in growth.